Investigation of the Role of Face Shape on the Flow Dynamics and Effectiveness of Face Masks - Tomas Solano; Kourosh Shoele (Fluids, 2022)
Due to the COVID-19 pandemic, face masks have been used extensively in society. The effectiveness of face masks depends on their material, design, and fit. With much research being focused on quantifying the role of the material, the design and fit of masks have been an afterthought at most. Recent studies, on the other hand, have shown that the mask fit is a significant factor to consider when specifying the effectiveness of the face mask. Moreover, the fit is highly dependent on face topology. Differences in face types and anthropometrics lead to different face mask fit. Here, computational fluid dynamics simulations employing a novel model for porous membranes (i.e., masks) are used to study the leakage pattern of a cough through a face mask on different faces. The three faces studied (female, male, and child) are characteristic faces identified in a previous population study. The female face is observed to have the most leakage through the periphery of the mask, which results in the lowest fitted filtration efficiency of the three faces. The male and child faces had similar gap profiles, leakage and fitted filtration efficiencies. However, the flow of the three faces differs significantly. The effect of the porosity of the mask was also studied. While all faces showed the same general trend with changing porosity, the effect on the child’s face was more significant.